Peran Strategis Koperasi Simpan Pinjam Sube Huter Nita dalam Mendorong Pertumbuhan Ekonomi UMKM: Suatu Kajian Kasus - Liam Alexander; Akbar Rizki Pratama (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
The Sube Huter Nita Savings and Loans Cooperative (KSP) has a strategic role in encouraging the economic growth of Micro, Small and Medium Enterprises (MSMEs). This study aims to explore and analyze the contributions and strategies implemented by KSP Sube Huter Nita in supporting the growth of MSMEs. The research method used is a qualitative approach through in-depth interviews, observation and documentation analysis. The research results show that KSP Sube Huter Nita has played an important role in providing financial access to MSMEs, including providing loans at competitive interest rates. Apart from that, cooperatives also provide training and assistance to MSME players to increase their capacity and competitiveness. In this way, KSP Sube Huter Nita effectively contributes to increasing the economic growth of MSMEs in its region.